Is the effect of ill health on school achievement among Swedish adolescents gendered? - Cristian Bortes; Mattias Strandh; Karina Nilsson (Elsevier, 2019)
This study investigates why the relationship between health problems requiring hospitalization between the ages of 13 and 16 and school achievement (school grades in 9th grade) in Sweden was stronger for girls than for boys. We reviewed previous research on gender differences in subjective health, health care utilization and medical drug treatment to identify mechanisms responsible for this gendered effect. The relationship was analysed using retrospective observational data from several national full-population registers of individuals born in 1990 in Sweden (n = 115 196), and ordinary least squares techniques were used to test hypotheses. We found that girls had longer stays when hospitalized, which mediated 15% of the interaction effect. Variability in drug treatment between boys and girls did not explain the gendered effect of hospitalization. The main mediator of the gendered effect was instead differences in diagnoses between boys and girls. Girls' hospitalizations were more commonly related to mental and behavioural diagnoses, which have particularly detrimental effects on school achievement. Keywords: Sweden, Child health, Adolescent health, Disease, Mental disorders, Academic achievement, Registries, Gender differences